Clinical interventions for women with schizophrenia: pregnancy. (21st June 2012) - Seeman, M. V.
<x xml:space="preserve">Abstract</x> Objective: A comprehensive treatment program for schizophrenia needs to include services to women of childbearing age that address contraception, pregnancy, and postpartum issues, as well as safe and effective parenting. To update knowledge in these areas, a summary of the recent qualitative and quantitative literature was undertaken. Method: The search terms 'sexuality, ''contraception, ''pregnancy, ''postpartum, ''custody, ' and 'parenting' were entered into PubMed, PsycINFO, and SOCINDEX along with the terms 'schizophrenia' and 'antipsychotic.' Publications in English for all years subsequent to 2000 were retrieved and their reference lists further searched in an attempt to arrive at a distillation of useful clinical recommendations. Results: The main recommendations to care providers are as follows: take a sexual history and initiate discussion about intimate relationships and contraception with all women diagnosed with schizophrenia. During pregnancy, adjust antipsychotic dose to clinical status, link the patient with prenatal care services, and help her prepare for childbirth. There are pros and cons to breastfeeding while on medication, and these need thorough discussion. During the postpartum period, mental health home visits should be provided. Parenting support is critical. Conclusion: The comprehensive treatment of schizophrenia in women means remembering that all women of childbearing age are potential new mothers.